2014
DOI: 10.1165/rcmb.2013-0363oc
|View full text |Cite
|
Sign up to set email alerts
|

FOXJ1 Prevents Cilia Growth Inhibition by Cigarette Smoke in Human Airway Epithelium In Vitro

Abstract: Airway epithelium ciliated cells play a central role in clearing the lung of inhaled pathogens and xenobiotics, and cilia length and coordinated beating are important for airway clearance. Based on in vivo studies showing that the airway epithelium of healthy smokers has shorter cilia than that of healthy nonsmokers, we investigated the mechanisms involved in cigarette smoke-mediated inhibition of ciliogenesis by assessing normal human airway basal cell differentiation in air-liquid interface (ALI) cultures in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
69
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 73 publications
(76 citation statements)
references
References 48 publications
7
69
0
Order By: Relevance
“…The reduced CBF (and the power of the detected signals) in the 3R4F (0.25)-exposed cultures was consistent with the observed reduced proportion of FoxJ1-positive stained cells. FoxJ1, a marker for ciliated cells, is a transcription factor that regulates cilia-related genes (Brekman et al, 2014). Overexpression of FoxJ1 was reported to halt the CS extract-mediated inhibition of cilia growth in differentiating normal human airway basal cells (Brekman et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The reduced CBF (and the power of the detected signals) in the 3R4F (0.25)-exposed cultures was consistent with the observed reduced proportion of FoxJ1-positive stained cells. FoxJ1, a marker for ciliated cells, is a transcription factor that regulates cilia-related genes (Brekman et al, 2014). Overexpression of FoxJ1 was reported to halt the CS extract-mediated inhibition of cilia growth in differentiating normal human airway basal cells (Brekman et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…FoxJ1, a marker for ciliated cells, is a transcription factor that regulates cilia-related genes (Brekman et al, 2014). Overexpression of FoxJ1 was reported to halt the CS extract-mediated inhibition of cilia growth in differentiating normal human airway basal cells (Brekman et al, 2014). Smoking is also associated with a shortening of airway cilia (Leopold et al, 2009;Brekman et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, diesel exhaust particles upregulate the mRNA levels of TSLP [115], which can promote maturation of myeloid DCs that support T H 2-type polarization [116]. Furthermore, numerous studies have shown that smokers exhibit impaired mucociliary clearance [117][118][119][120] because of the inhibitory effect of cigarette smoke compounds on the expression of genes involved in ciliogenesis [121]. In turn, an increase in barrier permeability may facilitate the access of aeroallergens to the submucosa and their interaction with resident DCs and ILC2s, as well as with recruited MCs, eosinophils, lymphocytes, and neutrophils [122].…”
Section: Effect Of Air Pollutants On the Airway Epithelium And Respirmentioning
confidence: 99%
“…The ratio of ciliated to secretory cells is tightly controlled at approximately 10 to 1 throughout the tracheobronchial tree, except for the most distal bronchioles, despite the fact that the proportions of basal cells are different going down the tracheobronchial tree and the secretory population changes from mucus-producing cells in the large airways to nonmucous secretory cells in the small airways (7,18). Studies in mice, and to a lesser extent in humans, have shown that ciliated cell differentiation is governed by a network of transcription factors and regulators, including FOXJ1, multicilin, cyclin O, Myb, and RFX family proteins (22)(23)(24)(25)(26)(27)(28)(29)(30). Differentiation to the secretory lineage is mediated by the Notch pathway, whereas generation of mucus-producing cells largely depends on activation of transcription factors SPDEF and FOXA3 (12,(31)(32)(33)(34) ( Figure 1D).…”
Section: Early Lung Abnormalities Associated With Smokingmentioning
confidence: 99%